Arthropod Fauna on Conocarpus Plants in Urban Landscapes (Journal of Agriculture and Biology, 2025)
The two species Conocarpus erectus (Buttonwood) and Conocarpus lancifolius (Damas tree) commonly known as Conocarpus are an important part of urban landscaping and reforestation due to their remarkable adaptability to various environmental conditions. These species are mainly found in tropical and subtropical regions and can withstand saline and arid environments. In this study arthropod biodiversity associated with Conocarpus was investigated in urban environment. A total of 13 distinct taxa of two arthropod classes: Insecta and Arachnida was identified belonging from orders Diptera, Hemiptera, Hymenoptera, Coleoptera, and Araneae. The arthropod fauna of Conocarpus showed multi-trophic structure, including herbivores (e.g., Myzus persicae, Agromyza pseudoreptans), predators (e.g., Phidippus sp., Colonus sp.), and parasitoids (e.g., Lycorina glaucomata, Macrocentrus sp.). Community diversity was moderate (S = 14, N = 37) with Shannon H′ = 2.4048, Simpson’s diversity (1−D) = 0.9174 and Pielou’s evenness J′ = 0.9112, indicating moderate richness coupled with high evenness.The biodiversity of Conocarpus plants suggests that they are valuable resources and habitats for a variety of arthropods in urban environments. The observed complex food chain highlights the significance of urban green areas as refuges for biodiversity in modified environment. This research contributes to urban ecology and can have a significant impact on conservation and urban planning.